Atratores artificiais em pescarias de emalhe artesanal no rio Araguaia, Brasil. - GENTIL, E. (2020)
The catch and selectivity effectiveness of two artificial attractors-AA (bright gray curly ribbon and green lightsticks) in gillnets was evaluated in order to increase the productivity and income of small scale fishermen. Five expeditions were carried on the Araguaia River, where the two AA treatments were applied to two thirds of the area of gillnets, leaving the remaining third without the use of attractors (control). For a better comparison, the catches were subdivided into ecological groups (carnivores, detritivores, herbivores and omnivores). 541 fish were caught, 197 in the curly ribbon, 177 lightstick and 167 in the control. Carnivorous fishes were predominant in all treatments (p = 0.025 for Kruskal Wallis test and p = 0.03 for Mann-Whitney test). The use of the ribbon and lighstick provided an increase in the catch of carnivorous teleost fish, providing a better gross profit margin. Due the low incomes and fragile economic situation of the fishing communities of Araguaia, the best technological choice in this study is the curly ribbon, as in addition to presenting better productivity, it is accessible low cost and easy to handle.